Management of complications related to colorectal endoscopic submucosal dissection - Tae-Geun Gweon; Dong-Hoon Yang (Korean Society of Gastrointestinal Endoscopy, 2023)
Compared to endoscopic mucosal resection (EMR), colonoscopic endoscopic submucosal dissection (C-ESD) has the advantages of higher en bloc resection rates and lower recurrence rates of colorectal neoplasms. Therefore, C-ESD is considered an effective treatment method for laterally spread tumors and early colorectal cancer. However, C-ESD is technically more difficult and requires a longer procedure time than EMR. In addition to therapeutic efficacy and procedural difficulty, safety concerns should always be considered when performing C-ESD in clinical practice. Bleeding and perforation are the main adverse events associated with C-ESD and can occur during C-ESD or after the completion of the procedure. Most bleeding associated with C-ESD can be managed endoscopically, even if it occurs during or after the procedure. More recently, most perforations identified during C-ESD can also be managed endoscopically, unless the mural defect is too large to be sutured with endoscopic devices or the patient is hemodynamically unstable. Delayed perforations are quite rare, but they require surgical treatment more frequently than endoscopically identified intraprocedural perforations or radiologically identified immediate postprocedural perforations. Post-ESD coagulation syndrome is a relatively underestimated adverse event, which can mimic localized peritonitis from perforation. Here, we classify and characterize the complications associated with C-ESD and recommend management options for them.